Lithium nickel-based composite oxides as positive electrode active materials for rechargeable lithium-ion batteries

A lithium nickel-based oxide with controlled soluble sulfur content and specific elemental ratios addresses the stability and capacity limitations of high nickel cathode materials, enhancing discharge capacity and cycle durability for lithium-ion batteries in electric vehicles.

JP7610004B2Active Publication Date: 2025-01-07UMICORE(BE) +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023538122
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-10-26
Publication Date
2025-01-07
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

High nickel-based cathode active materials for lithium-ion batteries used in electric vehicles and hybrid electric vehicles suffer from reduced cycle stability and limited discharge capacity, necessitating improvements for effective use in these applications.

Method used

A positive electrode active material comprising lithium nickel-based oxide with specific atomic ratios of Ni, Co, Mn, and optional elements like Al, B, and W, along with controlled amounts of soluble sulfur, is developed to enhance discharge capacity and stability.

Benefits of technology

The proposed material achieves a first discharge capacity of at least 207 mAh/g and improved cycle durability, making it suitable for high-capacity lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610004000009
    Figure 0007610004000009
  • Figure 0007610004000010
    Figure 0007610004000010
  • Figure 0007610004000011
    Figure 0007610004000011
Patent Text Reader

Abstract

The present invention provides a positive electrode active material powder for a lithium ion rechargeable battery, the positive electrode active material comprising Li, M', S, and O, wherein M' is Ni with a content x of 60.0 mol% to 95.0 mol% relative to M', Co with a content y of 0.0 mol% to 25.0 mol% relative to M', Mn with a content z of 0.0 mol% to 25.0 mol% relative to M', W with a content a of 0.05 mol% or more relative to M', and and D with a content b of 0.0 mol% to 2.0 mol%, D containing at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, F, Fe, Mg, Mo, Nb, Si, Sr, Ti, Y, V, Zn, and Zr, x, y, z, a, and b are measured by ICP, and x+y+z+a+b is 100.0 mol%, and the positive electrode active material contains soluble sulfur in a content of 0.30 mol% or more relative to M'.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for the preparation of sulfate ions (SO4 2- The present invention relates to a lithium nickel-based oxide positive electrode active material for lithium ion secondary batteries (LIBs) suitable for electric vehicles (EVs) and hybrid electric vehicles (HEVs), the lithium nickel-based oxide positive electrode active material comprising soluble sulfur-containing lithium transition metal oxide particles, also known as soluble sulfur-containing lithium transition metal oxide particles. [Background technology]

[0002] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a certain period of time.

[0003] In particular, the present invention relates to high nickel-based oxide positive electrode active materials (hereinafter referred to as "Ni-high compounds"), i.e., Ni-high compounds having an atomic ratio of Ni to M' of at least 75.0% (or 75.0 atomic %), preferably at least 77.5% (or 77.5 atomic %), more preferably at least 80% (or 80.0 atomic %).

[0004] In the framework of the present invention, atomic % means atomic percentage. Atomic % or "atomic percent" as an expression of the concentration of a given element means what percentage of all atoms in the claimed compound are atoms of that element.

[0005] The weight percentage (wt%) of the first element E in the substance (E wt1 ) is expressed as:

[0006]

number

[0007] The development of EVs and HEVs has created a demand for lithium-ion batteries suitable for such applications, and high-Ni class compounds are increasingly being developed as promising candidates for use as the positive electrode active material in LIBs due to their relatively low cost (vs. alternatives such as lithium cobalt-based oxides) and higher capacity at higher operating voltages.

[0008] Such high Ni compounds are already known, for example, from Japanese Patent No. 5584456(B2) (hereinafter referred to as "JP'456") or Japanese Patent No. 5251401(B2) (hereinafter referred to as "JP'401").

[0009] JP'456 specifies that SO4 should be added to the top of the particles of the high Ni compound with a content in the range of 1000ppm to 4000ppm. 2- ions (e.g., sulfate radicals in the JP '456 expression). The calculated molar content of soluble sulfur ranges from 0.1 mol% to 0.4 mol% based on the total molar content of Ni, Co, and Mn. JP '456 explains that when the amount of sulfate radicals is within the above range, the capacity retention and discharge capacity properties of the compound are increased. However, when the amount of sulfate radicals is less than the above range, the capacity retention decreases, and when the amount is greater than the above range, the discharge capacity decreases.

[0010] JP '401 teaches that by applying a sulfate coating, particularly a lithium sulfate coating, to primary particles, the secondary particles resulting from the agglomeration of the sulfate-coated primary particles can be engineered to have a specific pore structure that allows the high Ni compounds made from the secondary particles to have higher cycle durability and higher initial discharge capacity. JP '401 further explains that such a specific pore structure is achieved upon washing away the sulfate coating.

[0011] Although high-Ni compounds are promising in terms of the above advantages, they also have drawbacks such as reduced cycle stability due to the high Ni content.

[0012] As examples of these shortcomings, prior art high Ni compounds have either a low first discharge capacity of less than 180 mAh / g (JP'456) or a limited capacity retention of up to 86% (JP'401).

[0013] Therefore, there is currently a need to achieve high Ni compounds with sufficiently high first discharge capacity (i.e., at least 207 mAh / g), which, according to the present invention, is a prerequisite for using such high Ni compounds in LIBs suitable for (H)EV applications.

[0014] The object of the present invention is to provide an improved first discharge The object is to provide a positive electrode active material having a large capacity.

[0015] Acknowledgements This invention was made with the support of the Materials / Parts Technology Development Program through the Korea Industrial Technology Assessment Agency, funded by the Ministry of Trade, Industry and Energy (MOTIE, Republic of Korea). [Project name: Development of 8C rate class high output (high discharge rate) lithium ion secondary battery / Project number: 20011287 / Contribution rate: 100%] Summary of the Invention

[0016] The object is to provide a cathode active material for a lithium ion battery, the cathode active material comprising Li, M', S and O, wherein M' is Ni with a content x of 60.0 mol% to 95.0 mol% relative to M'; Co with a content y of 0.0 mol% to 25.0 mol% relative to M'; Mn with a content z of 0.0 mol% to 25.0 mol% relative to M'; W with a content a of 0.05 mol% to 0.50 mol% relative to M'; D having a content b of 0.0 mol % to 2.0 mol % relative to M', D containing at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, F, Fe, Mg, Mo, Nb, Si, Sr, Ti, Y, V, Zn, and Zr; x, y, z, a, and b are measured by ICP; x+y+z+a+b is 100.0 mol%, This is achieved by providing a positive electrode active material containing soluble sulfur in a content of 0.30 mol % to 2.00 mol % relative to M'.

[0017] It should be noted that when an element is stated to be present in a content between 0.0 mol% and another value, this means that the element may not be present at all, in other words, the element is optional.

[0018] Preferably, the soluble sulfur is SO 2- or, more precisely, as sulfates, such as the Li2SO4 form as determined by XPS. 2- Or it can be related to the sulfite form, or more precisely as sulfite.

[0019] The soluble sulfur content is readily determined by ICP analysis after washing the cathode active material of the present invention with water according to Session A) ICP Analysis in the Detailed Description.

[0020] In the framework of the present invention, ppm means parts per million for units of concentration, representing 1 ppm = 0.0001% by weight.

[0021] Furthermore, within the framework of the present invention, the term "sulfur" refers to the presence of sulfur atoms or elemental sulfur in the claimed cathode active material.

[0022] The present invention relates to the following embodiments.

[0023] EMBODIMENT 1 In a first aspect, the present invention provides an active cathode material for a lithium ion battery, the active cathode material comprising Li, M′, S, and O, wherein M′ is - Ni with a content x of 60.0 mol% to 95.0 mol% relative to M'; - Co with a content y of 0.0 mol% to 25.0 mol% relative to M'; - Mn with a content z of 0.0 mol% to 25.0 mol% relative to M'; - W with a content a of 0.05 or more relative to M'; D, with a content b of 0.0 mol% to 2.0 mol% relative to M', wherein D contains at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, F, Fe, Mg, Mo, Nb, Si, Sr, Ti, Y, V, Zn and Zr; - x, y, z, a, and b are measured by ICP; -x+y+z+a+b is 100.0 mol%, The positive electrode active material relates to a positive electrode active material containing soluble sulfur in a content of 0.30 mol % or more relative to M'.

[0024] Preferably, the positive electrode active material contains soluble sulfur in a content of 0.30 mol % to 2.00 mol % relative to M'.

[0025] Preferably, the soluble sulfur is present in the positive electrode material in a content of 0.50 mol % to 1.50 mol % relative to M', more preferably 0.50 mol % to 1.00 mol % relative to M'.

[0026] Preferably, the soluble sulfur content is equal to the reduction in S content relative to M' as determined by ICP after contacting (or dispersing) the cathode active material powder in (or in) deionized water several times for at least 5 minutes (by stirring) at 25° C., filtering the cathode active material powder, and drying the cathode active material powder.

[0027] In a preferred embodiment, the Ni is present in a content x of 75 mol % or more, preferably at least 80 mol %.

[0028] In a preferred embodiment, the Ni is present in a content x of less than or equal to 90 mol %.

[0029] In a preferred embodiment, the Co is present in a content y equal to or greater than 5.0 mol %.

[0030] In a preferred embodiment, the Co is present in a content y less than or equal to 10.0 mol %.

[0031] In a preferred embodiment, the Ni is present in a content x of 75 mol % or more, preferably at least 80 mol %.

[0032] Preferably, a is at most 0.50 mol %.

[0033] In a preferred embodiment, the content a of W is 0.05 mol % to 0.50 mol % with respect to M'.

[0034] In another embodiment, the content a of W is 0.10 mol % to 0.30 mol % with respect to M'.

[0035] EMBODIMENT 2 In the second embodiment, preferably according to the first embodiment, the positive electrode active material contains Al in a content of 0.10 mol % to 1.00 mol % relative to M'.

[0036] Preferably, the positive electrode active material contains 0.20 mol % to 0.50 mol % of Al relative to M'.

[0037] Preferably, the positive electrode active material contains Al in a content of 0.10 mol % or more, preferably 0.20 mol % or more, relative to M'.

[0038] Preferably, the positive electrode active material contains Al in a content of at most 1.0 mol %, preferably at most 0.50 mol %, relative to M'.

[0039] For the sake of completeness, it is emphasized that Al is included in D and, consequently, the content of Al is included in the parameter b.

[0040] Therefore, in other words, in a preferred embodiment, D contains Al in a content of up to 1.0 mol %, preferably up to 0.50 mol %, relative to M'.

[0041] In a preferred embodiment, D contains Al in an amount of 0.10 mol % or more, preferably 0.20 mol % or more, relative to M'.

[0042] EMBODIMENT 3 In the third embodiment, preferably according to the first or second embodiment, the positive electrode active material contains B in a content of 0.05 mol % to 1.50 mol % relative to M'.

[0043] Preferably, the positive electrode active material contains B in a content of at least 0.05 mol %, more preferably at least 0.1 mol %, relative to M'.

[0044] Preferably, the positive active material contains B in a content of up to 1.5 mol %, preferably up to 1.0 mol %, relative to M'.

[0045] For the sake of completeness, it is emphasized that B is included in D and, consequently, the content of B is included in the parameter b.

[0046] Therefore, in other words, in a preferred embodiment, D contains B in a content of up to 1.5 mol %, more preferably 1.0 mol %, even more preferably up to 0.50 mol %, relative to M'.

[0047] In a preferred embodiment, D contains B in a content of 0.05 mol % or more, preferably 0.10 mol % or more, relative to M'.

[0048] EMBODIMENT 4 In a third embodiment, preferably according to embodiments 1 to 3, the substance is - the S content S, determined by ICP analysis and expressed as a mole fraction compared to the sum of x, y and z A and W content W A , - the average S fraction, S, determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn, and Ni measured by XPS analysis B and the average W fraction W B , having -ratio S B / S A > 1.0, -ratio W B / W A >1.0.

[0049] Preferably, the ratio S B / S A is at least 1.5 and at most 600, and more preferably, the ratio W B / W A is at least 1.5 and at most 700.

[0050] Preferably, the ratio S B / S A is at least 50 and at most 550, more preferably, S B / S A is at least 100 and at most 500.

[0051] Preferably, the ratio W B / W Ais at least 50 and at most 700, more preferably W B / W A is at least 100 and at most 650.

[0052] In addition, S B and S A is the total sulfur content, thus including the content of soluble sulfur.

[0053] EMBODIMENT 5 In a fifth embodiment, preferably according to embodiments 1 to 4, the substance is -Al, determined by ICP analysis and expressed as mole fraction relative to the sum of x, y and z A Content Al A - the average Al fraction, determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni measured by XPS analysis, Al B , having -Compared to Al B / Al A >1.0.

[0054] Preferably, the ratio Al B / Al A must be at least 3.0 and at most 2500.

[0055] Preferably, the ratio Al B / Al A is at least 200 and at most 2400, more preferably Al B / Al A is at least 300 and at most 2300.

[0056] EMBODIMENT 6 In a sixth embodiment, preferably according to embodiments 1 to 5, the substance comprises - B content, determined by ICP analysis and expressed as a mole fraction relative to the sum of x, y and z A - the average B fraction, determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn and Ni measured by XPS analysis; B having -ratio B B / B A >1.0.

[0057] Preferably, the ratio B B / B A is at least 100 and at most 1500.

[0058] Preferably, the ratio B B / B A is at least 200 and at most 1400, and more preferably, B B / B A is at least 300 and at most 1200.

[0059] Specifically, in any of the first to sixth embodiments, S B , W B , Al B , and B B are the average fractions of S, W, Al, and B, respectively, measured in a region defined between a first point on the outer edge of a particle of a positive electrode material powder according to the present invention and a second point at a distance from the first point, the distance separating the first point and the second point being equal to the XPS penetration depth, D being 1.0 to 10.0 nm. Specifically, the penetration depth is the distance along an axis perpendicular to an imaginary line tangent to the outer edge and passing through the first point.

[0060] The outer edge of a particle is, within the framework of the present invention, the boundary or outer limit which distinguishes the particle from its external environment.

[0061] The present invention relates to the use of the positive electrode active material according to any one of the above embodiments 1 to 6 in a battery.

[0062] The present invention also provides a method for producing a positive electrode active material according to any one of the above-described embodiments 1 to 6, - preparing a first sintered lithium transition metal based oxide compound; - mixing said first sintered lithium transition metal based oxide compound with a tungsten source, preferably WO3, with a sulfate ion source, preferably Al2(SO4)3 and / or H2SO4, and with water, thereby obtaining a mixture; heating the mixture in an oxidizing atmosphere in a furnace at a temperature between 350° C. and less than 500° C., preferably at most 450° C., for a time between 1 hour and 20 hours to obtain the cathode active material powder according to the invention.

[0063] Preferably, a lithium metal-based oxide compound is mixed with a boron source, preferably H3BO3, along with a source of tungsten and a source of sulfate ions. [Brief description of the drawings]

[0064] [Figure 1] This is an SEM image of EX1.3. [Figure 2a] These are the Al2p and Ni3p peaks in the XPS spectrum of EX1.4. [Figure 2b] This is the S2p peak in the XPS spectrum of EX1.4. [Figure 2c] This is the W2f peak in the XPS spectrum of EX1.4. [Figure 2d] This is the B1s peak in the XPS spectrum of EX3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0065] To enable the practice of the invention, preferred embodiments are described in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. The invention includes numerous alternatives, modifications, and equivalents that will be apparent from consideration of the following detailed description and the accompanying drawings.

[0066] A) ICP analysis A 1)ICP measurement The Li, Ni, Mn, Co, Al, B, W, and S contents of the positive electrode active material powder are measured by Inductively Coupled Plasma (ICP) method by using Agillent ICP720-ES. In an Erlenmeyer flask, 2 g of product powder sample is dissolved in 10 mL of high purity hydrochloric acid. The flask is covered with glass and heated on a hot plate at 380 °C until the precursor is completely dissolved. After cooling to room temperature, the solution in the Erlenmeyer flask is poured into a 250 mL volumetric flask. Then, the volumetric flask is filled with deionized water up to the 250 mL mark, followed by thorough homogenization. An appropriate amount of the solution is taken out with a pipette and transferred to a 250 mL volumetric flask for the second dilution, and the volumetric flask is filled with an internal standard and 10% hydrochloric acid up to the 250 mL mark, followed by homogenization. Finally, this 50 mL solution is used for ICP measurement.

[0067] A2) Soluble sulfur measurement To investigate the soluble S content in the lithium transition metal oxide particles according to the present invention, a washing and filtering process is carried out. 5 g of the positive electrode active material powder and 100 g of ultrapure water are weighed into a beaker. The electrode active material powder is dispersed in water at 25°C for 5 minutes using a magnetic stirrer. The dispersion is vacuum filtered, and the dried powder is analyzed by the above ICP measurement to measure the amount of soluble S-containing compounds.

[0068] B) X-ray photoelectron spectroscopy In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.

[0069] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-A+ spectrometer (Thermo Scientific, https: / / www.thermofisher.com / order / catalog / product / IQLAADGAAFFACVMAHV). Monochromatic Al KA radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. A broad survey scan to identify the elements present on the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection. Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.

[0070] Curve fitting was performed with CasaXPS version 2.3.19PR1.0 (Casa Software, http: / / www.casaxps.com / ) using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 1a. The lineshape GL(30) is a Gaussian / Lorentzian product formula with a 70% Gaussian line and a 30% Lorentzian line. LA(A,B,m) is the asymmetric lineshape, where A and B define the tail broadening of the peak and m defines the width.

[0071] [Table 1]

[0072] For the Al, S, Co, and W peaks, constraints are set for each defined peak according to Table 1b. Ni3p (including Ni3p3, Ni3p1, Ni3p3 satellite, and Ni3p1 satellite) and W5p3 are not quantified.

[0073] [Table 2]

[0074] The surface contents of Al, S, B, and W as measured by XPS are expressed as the mole fraction of Al, S, B, and W, respectively, in the surface layer of the particle divided by the total content of Ni, Mn, and Co in that surface layer, and are calculated as follows: Fraction of Al = Al B =Al(atomic%) / (Ni(atomic%)+Mn(atomic%)+Co(atomic%)) Fraction of S = S B =S(atomic%) / ((Ni(atomic%)+Mn(atomic%)+Co(atomic%)) Fraction of W = W B = W (atomic %) / ((Ni (atomic %) + Mn (atomic %) + Co (atomic %)) Fraction of B = B B =B(atomic%) / ((Ni(atomic%)+Mn(atomic%)+Co(atomic%))

[0075] The information of the XPS peak positions can be easily obtained in the area and component report specifications after fitting is performed. The XPS graphs of Al, S, W, and B are shown in Figures 2a, 2b, 2c, and 2d, respectively.

[0076] C) Coin Cell Test C1) Coin cell fabrication For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, conductor (Super P, Timcal), and binder (KF#9305, Kureha) in a solvent (NMP, Mitsubishi) with a weight ratio of 96.5:1.5:2.0 is prepared by a high-speed homogenizer. The homogenized slurry is spread on one side of an aluminum foil using a doctor blade coater with a gap of 170 μm. The foil coated with the slurry is dried in an oven at 120 °C and then pressed using a calendar tool. It is then dried again in a vacuum oven to completely remove the residual solvent in the electrode film. The coin cell is assembled in an argon-filled glove box. A separator (Celgard 2320) is placed between the positive electrode and the lithium foil as the negative electrode. 1M LiPF6 in EC / DMC (1:2) is used as the electrolyte and dropped between the separator and the electrode. The coin cell is then completely sealed to prevent electrolyte leakage.

[0077] C2) Test method The test method is a conventional "constant cut-off voltage" test. Conventional coin cell testing in this invention follows the schedule shown in Table 2. Each cell is cycled at 25°C using a Toscat-3100 computer-controlled galvanostatic cycling station (Toyo). This schedule uses a 1C current definition of 220mA / g. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC) at a C rate of 0.1C in the window range of 4.3V to 3.0V / Li metal.

[0078] The irreversible capacity IRRQ is expressed as a percentage as follows:

[0079]

number

[0080] [Table 3]

[0081] The invention is further illustrated in the following (non-limiting) examples.

[0082] Comparative Example 1 Formula Li 1+d (Ni 0.80 Mn 0.10 Co 0.10 ) 1-d The high Ni compound CEX1 with O2 is obtained by carrying out a double sintering process, which is a solid-state reaction between a lithium source and a transition metal source, as follows: 1) Coprecipitation: The metal composition Ni was obtained by coprecipitation process with nickel-manganese-cobalt sulfate, sodium hydroxide, and ammonia mixed in a large continuous stirred tank reactor (CSTR). 0.80 Mn 0.10 Co 0.10 A transition metal-based oxide-hydroxide precursor having the formula: 2) Blending: A transition metal based hydroxide precursor is homogeneously blended with LiOH as the lithium source in a commercial blending apparatus with a lithium to metal M' (Li / M') ratio of 1.01. 3) First sintering: The blend is sintered at 730° C. for 12 hours under oxygen atmosphere. The sintered powder is crushed, classified and sieved to obtain the sintered intermediate product. 4) Second sintering: The intermediate product is sintered at 830°C for 12 hours in an oxygen atmosphere to obtain a sintered powder of agglomerated primary particles. The sintered powder is crushed, classified and sieved to obtain a sintered powder of the formula Li 1.005 M' 0.995 O2 (d=0.005), where M'=Ni 0.80 Mn 0.10 Co 0.10 CEX1 has a D50 of 12.0 μm and a span of 1.24. CEX1 contains a trace amount of sulfur obtained from the metal sulfate source in the coprecipitation process of step 1).

[0083] Optionally, a dopant source can be added together with the lithium source in the co-precipitation process of step 1) or in the blending process of step 2) For example, a dopant can be added to improve the electrochemical properties of the positive electrode active material powder product.

[0084] CEX1.1 is not according to the present invention.

[0085] CEX1.2, which is not according to the present invention, is prepared by the following procedure. Step 1) Wet mixing: CEX1.1 is mixed with an aluminum sulfate solution prepared by dissolving 1000 ppm Al from Al2(SO4)3 powder in deionized water at 3.5 wt% with respect to the weight of CEX1.1. Step 2) Heating: The mixture obtained from step 1) is heated at 385° C. for 8 hours under oxygen atmosphere, followed by crushing and sieving to obtain CEX1.2 containing about 1000 ppm Al with respect to the total weight of EX1.2.

[0086] Example 1 EX1.1 according to the present invention is prepared by the following steps: Step 1) Dry Mixing: CEX1.1 is dry mixed with 2000 ppm W from WO3 powder to obtain a dry mix.

[0087] Step 2) Wet mixing: Obtain a wet mixture by mixing the dry mixture from step 1) with an aluminum sulfate solution prepared by dissolving 600 ppm Al from Al2(SO4)3 powder in 3.5 wt of deionized water with respect to the weight of CEX1.1.

[0088] Step 3) Heating: The mixture obtained from step 2) is heated at 385° C. for 8 hours under oxygen atmosphere, followed by grinding and sieving to obtain EX1.2.

[0089] EX1.2 according to the invention is prepared according to the same method as EX1.1, except that 3000 ppm W is added in step 1).

[0090] EX1.3 according to the present invention is prepared according to the same method as EX1.1, except that in step 1) 4000 ppm of W is added. SEM images of EX1.3 were taken (see FIG. 1).

[0091] EX1.4 according to the invention is prepared according to the same method as EX1.1, except that in step 2) 800 ppm Al is added.

[0092] EX1.5 according to the present invention is prepared according to the same method as EX1.4, except that 3000 ppm W is added in step 1).

[0093] EX1.6 according to the invention is prepared according to the same method as EX1.4, except that 4000 ppm W is added in step 1).

[0094] Example 2 EX2 according to the present invention is prepared by the following steps: Step 1) Dry Mix: CEX1.1 is dry mixed with 4500 ppm W from WO3 powder to obtain a dry mix.

[0095] Step 2) Wet mixing: Obtain a wet mixture by mixing the dry mixture from step 1) with 0.5 mol% S from a sulfuric acid solution prepared by dissolving concentrated H2SO4 solution (98% concentration) in deionized water at 3.5 wt% relative to the weight of CEX1.1.

[0096] Step 3) Heating: The mixture obtained from step 2) is heated at 285° C. for 8 hours under oxygen atmosphere, followed by grinding and sieving to obtain EX1.2.

[0097] Comparative Example 2 CEX2, not according to the invention, is made according to the same method as EX2, except that the wet mixing step 2) is omitted.

[0098] Example 3 EX3 according to the present invention is prepared by the following procedure: Step 1) Dry mixing: CEX1.1 is dry mixed with 500 ppm B from H3BO3 and 4500 ppm W from WO3 powder to obtain a dry mixture.

[0099] Step 2) Wet mixing: The dry mixture from step 1) is mixed with an aluminum sulfate solution prepared by dissolving 1000 ppm Al from Al2(SO4)3 powder in deionized water at 3.5 wt% with respect to the weight of the dry mixture.

[0100] Step 3) Heating: The wet mixture obtained from step 2) is heated at 385° C. for 8 hours under oxygen atmosphere, followed by grinding and sieving to obtain EX3.

[0101] [Table 4]

[0102] [Table 5]

[0103] [Table 6]

[0104] Table 3 summarizes the compositions of Al, W, and soluble S in the examples and comparative examples, as well as their corresponding electrochemical properties. EX1.1 to EX1.6 and EX2, in which the content of W is 0.05 mol% to 0.50 mol% relative to M' and the content of soluble S is 0.30 mol% to 2.00 mol% relative to M', can achieve the object of the present invention to provide a cathode active material with an improved first charge capacity of at least 207 mAh / g. Furthermore, EX3 also contains 0.4 mol% B, which further improves the electrochemical properties.

[0105] Table 4 summarizes the XPS analysis results of CEX1.2, EX1.4, and EX3, showing the atomic ratios of Al, S, B, and W relative to the total atomic fractions of Ni, Mn, and Co. The table also compares the results with the ICP results. Atomic ratios higher than 0 indicate that the Al, S, B, and W are present at the surface of the cathode active material, in conjunction with the XPS measurements, where the signal is obtained from the top few nanometers (e.g., 1 nm to 10 nm) of the sample, i.e., the surface layer. On the other hand, the atomic ratios of Al, S, B, and W obtained from the ICP measurements are from the whole particle. Thus, an XPS to ICP ratio greater than 1 indicates that the elements Al, S, B, or W are mainly present at the surface of the cathode active material. XPS to ICP ratios higher than 1 are observed for Al, S, and W in EX1.4. Similarly, XPS to ICP ratios higher than 1 are observed for Al, S, B, and W in EX3.

[0106] Table 5 shows the XPS peak positions of Al2p, S2p3, W4f7, and B1s for CEX1.2, EX1.4, and EX3 obtained according to the XPS analysis described in this invention.

Claims

1. 1. A cathode active material for a lithium ion rechargeable battery, the cathode active material comprising Li, S, M′, and O, where M′ is - Ni with a content x of 60.0 mol % to 95.0 mol % relative to M', - Co with a content y of 0.0 mol % to 25.0 mol % relative to M', - Mn with a content z between 0.0 mol % and 25.0 mol % relative to M', - W with a content a of 0.05 mol% or more relative to M'; D with a content b of 0.0 mol % to 2.0 mol % relative to M', where D contains at least one element from the group consisting of Al, B, Ba, Ca, Cr, F, Fe, Mg, Mo, Nb, Si, Sr, Ti, Y, V, Zn and Zr, - x, y, z, a, and b are measured by ICP; -x+y+z+a+b is 100.0 mol%, The positive electrode active material contains soluble sulfur in a content of 0.30 mol % or more relative to M', an active cathode material, wherein the soluble sulfur content is equal to the reduction in S content relative to M' as determined by ICP after dispersing the active cathode material in deionized water to obtain a solution, stirring the solution for at least 5 minutes at 25° C., filtering the active cathode material, and drying the active cathode material.

2. 2. The positive electrode active material according to claim 1, wherein x is 75 mol% to 90 mol%.

3. 3. The positive electrode active material according to claim 1, wherein the content of the soluble sulfur is 0.50 mol % or more with respect to M'.

4. The positive electrode active material according to any one of claims 1 to 3, wherein a is 0.10 mol% or more.

5. The positive electrode active material according to any one of claims 1 to 4, comprising Al in an amount of 0.10 mol% or more relative to M'.

6. The positive electrode active material according to any one of claims 1 to 5, comprising Al in an amount of up to 1.0 mol% relative to M'.

7. The positive electrode active material according to any one of claims 1 to 6, comprising B in an amount of at least 0.05 mol% relative to M'.

8. The positive electrode active material according to any one of claims 1 to 7, comprising B in a content of up to 1.5 mol% relative to M'.

9. - the S content S, determined by ICP analysis and expressed as a mole fraction relative to the sum of x, y and z A and W content W A , - the average S fraction S determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn, and Ni measured by XPS analysis B and the average W fraction W B , having - ratio S B / S A > 1.0, -ratio W B / W A > 1.0, The positive electrode active material according to any one of claims 1 to 8.

10. The ratio S B / S A is at least 1.

5.

11. The ratio W B / W A The positive electrode active material according to claim 9 or 10, wherein the σ is at least 1.

5.

12. The ratio S B / S A The positive electrode active material according to any one of claims 9 to 11, wherein the maximum molecular weight is 600.

13. The ratio W B / W A The positive electrode active material according to any one of claims 9 to 12, wherein the maximum molecular weight is 700.

14. - the Al content, determined by ICP analysis and expressed as a mole fraction relative to the sum of x, y and z, Al A , - the average Al fraction, determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn, and Ni measured by XPS analysis; B , having -Al ratio B / Al A > 1.0, The positive electrode active material according to any one of claims 1 to 13.

15. The ratio Al B / Al A is at least 3.

0.

16. The ratio Al B / Al A The positive electrode active material according to claim 14 or 15, wherein the maximum molecular weight is 2,400.

17. The positive electrode active material according to any one of claims 1 to 16, comprising the soluble sulfur in an amount of 2.00 mol% or less relative to M'.

18. The positive electrode active material according to any one of claims 1 to 17, comprising the soluble sulfur in an amount of 1.00 mol% or less relative to M'.

19. The positive electrode active material according to any one of claims 1 to 18, wherein a is 0.50 mol% or less.

20. The positive electrode active material according to any one of claims 1 to 19, wherein y is 5 mol% to 10 mol% relative to M'.

21. - B content B, determined by ICP analysis and expressed as a mole fraction compared to the sum of x, y and z A , - the average B fraction determined by XPS analysis and expressed as a mole fraction compared to the sum of the fractions of Co, Mn, and Ni measured by XPS analysis B having - ratio B B / B A > 1.0, The positive electrode active material according to any one of claims 1 to 20.

22. The ratio B B / B A is at least 100.

23. The ratio B B / B A The positive electrode active material according to claim 21 or 22, wherein the maximum molecular weight is 1,500.

24. A method for producing a positive electrode active material according to any one of claims 1 to 23, comprising the steps of: - preparing a first sintered lithium transition metal based oxide compound; - mixing said first sintered lithium transition metal based oxide compound with a source of tungsten, a source of sulfate ions, and water, thereby obtaining a mixture; - heating said mixture in an oxidizing atmosphere in a furnace at a temperature between 350°C and less than 500°C for a time period between 1 hour and 20 hours to obtain said cathode active material according to the invention; A method comprising:

25. 25. The method of claim 24, wherein a lithium metal based oxide compound is mixed with a source of boron and a source of tungsten and a source of sulfate ions.

26. A battery comprising the positive electrode active material according to any one of claims 1 to 23.

27. 27. Use of the battery of claim 26 in an electric or hybrid electric vehicle.

28. The positive electrode active material according to claim 5 , which contains Al in an amount of 0.20 mol % or more relative to M′.

29. The positive electrode active material according to claim 6 , which contains Al in an amount of up to 0.50 mol % relative to M′.

30. The positive electrode active material according to claim 7 , comprising B in a content of at least 0.1 mol % relative to M′.

31. The positive electrode active material according to claim 8 , comprising B in a content of up to 1.0 mol % relative to M′.

32. The positive electrode active material according to claim 19 , wherein a is 0.30 mol % or less.

33. The tungsten source is WO 3 and the sulfate ion source is Al 2 (SO 4 ) 3 and / or H 2 SO 4 and The method of claim 24, wherein the mixture is heated at a temperature of from 350°C to 450°C.

34. The boron source is H 3 B.O. 3 26. The method of claim 25, wherein:

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, manufacturing method thereof, and nonaqueous electrolyte secondary battery arranged by use of positive electrode active material

    JP2015216105A

  • Nonaqueous electrolyte secondary battery

    WO2012081518A2